101 Rules of Thumb for Sustainable Buildings and Cities - Heywood, Huw (RIBA Publications, 2016)
People across the world are becoming more aware of the need for the buildings and cities they live and work in to be sustainable, but the issue of how to be sustainable can seem a confusing and complex one. These rules of thumb provide universal guidelines for the sustainable design of both buildings and the urban realm. It's a global primer and textbook for anyone interested in understanding sustainability in the built environment, an ideal starting point for students as well as an aide memoir for more experienced readers and practitioners interested in this field.